Reconstructing Long-Term Changes in Avian Populations Using Lake Sediments: Opening a Window Onto the Past - Duda, Matthew P.; Hargan, Kathryn E.; Michelutti, Neal; Blais, Jules M.; Grooms, Christopher; Gilchrist, H. Grant; Mallory, Mark L.; Robertson, Gregory J.; Smol, John P. (Frontiers in Ecology and Evolution, 2021)
The lack of long-term monitoring data for many wildlife populations is a limiting factor in establishing meaningful and achievable conservation goals. Even for well-monitored species, time series are often very short relative to the timescales required to understand a population’s baseline conditions before the contemporary period of increased human impacts. To fill in this critical information gap, techniques have been developed to use sedimentary archives to provide insights into long-term population dynamics over timescales of decades to millennia. Lake and pond sediments receiving animal inputs (e.g., feces, feathers) typically preserve a record of ecological and environmental information that reflects past changes in population size and dynamics. With a focus on bird-related studies, we review the development and use of several paleolimnological proxies to reconstruct past colony sizes, including trace metals, isotopes, lipid biomolecules, diatoms, pollen and non-pollen palynomorphs, invertebrate sub-fossils, pigments, and others. We summarize how animal-influenced sediments, cored from around the world, have been successfully used in addressing some of the most challenging questions in conservation biology, namely: How dynamic are populations on long-term timescales? How may populations respond to climate change? How have populations responded to human intrusion? Finally, we conclude with an assessment of the current state of the field, challenges to overcome, and future potential for research.